การเร่งการเติบโตต้นหม่อนด้วยเทคนิคน้ำที่กระตุ้นด้วยพลาสมา - สวรุจ ขาวอิ่น (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The objective of this study, “Enhancing Germination Rate of Mulberry by Plasma Activated Water Technique” is to increase reactive nitrogen species (RNS), which is in the form of Nitrate (NO3), in water by activation of Plasma Activated Water (PAW) on Mulberry Sakhon Nakhon 72. The method used in this study are that of the application of full factorial experiment with Center Point. The study is on three main parameters which are electric power (watt), nitrogen gas flowrate and activated time in relation to the Enhancing of reactive nitrogen species (RNS) quantity and leaf area. The Image processing technique shall be used regarding the measurement of leaf area. Regarding to the experiment, it was found that those three factors affected on reactive nitrogen species (RNS) significantly. With electric power of 500 Watt, the nitrogen gas flowrate of 2.5 Liters per minutes and discharge time of 10 minutes, increased the quantity of reactive nitrogen species (RNS) the most, which produced the nitrate concentration of 33.36 milligrams per liter by average. However, regarding the growth acceleration on mulberry, it was found that there are only 2 significant parameters which are electric power and discharge time. It is noted that, by using response optimizer method, the most suitable value used are 500 watts of electric power with 0.5 liter per minutes of flowrate and 10 minutes discharged time, could increase the leaf area of 58.4 percent more than the controlled group without plasma activated water.